Peran dan fungsi agama dalam masyarakat - Ana, Tina Silfi (Maliki Interdisciplinary Journal, 2025)
This text discusses the concept of roles and functions of religion in the context of society and individuals. Etymologically, the role means the expected behavioral device in the community, while the function refers to the use or task done. Religion is identified as an important element of individual and social identity, which regulates behavior and moral law. There are several roles of religion in society, including motivators, innovators, integrators, sublimators, and cultural inspiration sources. In addition, religion serves as a source of value in individuals to maintain decency, overcome frustration, and fulfill curiosity. At the community level, religious functions are divided into eight categories, namely educational, rescue, atmosc, social control, solidarity binding, transformation, creativity, and sublimation. This explanation highlights the complexity of the roles and functions of religion in forming individual behavior and social dynamics in society.